The effect of a simple checklist on frequent pre‐induction deficiencies - Øyvind Thomassen; Guttorm Brattebø; Eirik Søfteland; HM Lossius; J‐K. HELTNE (2010)
A substantial proportion of anaesthesia-related adverse events are preventable by identification and correction of errors in planning, communication, fatigue, stress, and equipment. The aim of this study was to develop and implement a pre-induction checklist in order to identify and solve problems before induction of anaesthesia.The checklist was developed in a stepwise manner using a modified Delphi technique, literature search, expert's opinion, and a pilot version, and then implemented in a clinical environment during a 13-week study period. Each list was registered and analysed using statistical process control. The checklist was mandatory, but emergency cases were excluded.The checklist, containing 26 items, was used in 502 (61%) of a total of 829 inductions. Eighty-five checklists (17%) identified one or more missing items. The number of missing items decreased significantly throughout the study period. The most important missing items were lack of a second laryngoscope available, introducer not having been fitted to the endotracheal tube, the endotracheal tube cuff not having been tested, and no separate ventilation bag being available. It took a median of 88.5 s (range 52-118) to perform the checklist when no items were missing. The pre-induction time was the same before and after the checklist was introduced (25.1 vs. 24.3 min, P50.25).It is possible to develop, introduce, and use a pre-induction checklist even in a hectic and stressful clinical environment. The checklist identified and reduced a surprisingly large number of missing items required in a standard induction protocol.